Structural, Optical, and Morphological Study of the Zinc Oxide Nano-Thin Films with Different Thickness Prepared by Pulsed Laser Deposition Technique - Hasan, Fatima A.; Hussein, Mohammed T.; Abdulsattar, Mudar A. (Iraqi Journal of Science, 2022)
The goal of this investigation is to prepare zinc oxide (ZnO) nano-thin films by pulsed laser deposition (PLD) technique through Q-switching double frequency Nd:YAG laser (532 nm) wavelength, pulse frequency 6 Hz, and 300 mJ energy under vacuum conditions (10-3 torr) at room temperature. (ZnO) nano-thin films were deposited on glass substrates with different thickness of 300, 600 and 900 nm. ZnO films, were then annealed in air at a temperature of 500 °C for one hour. The results were compared with the researchers' previous theoretical study. The XRD analysis of ZnO nano-thin films indicated a hexagonal multi-crystalline wurtzite structure with preferential growth lines (100), (002), (101) for ZnO nano-thin films with different thicknesses of un-annealed samples and after annealing. While the UV-Visible spectrum manifested that the ZnO has a high absorption at UV range and wide energy gap values of (3.4, 3.42, and 3.46 eV) for the three thicknesses. The surface topography of the films evinced a rough surface which increased with increasing thickness, whereas the grain size decreased, and the average grain size was about 56.68 nm. Furthermore, the nano-thin films showed a granular morphology with a tendency to form smaller particles with increasing thickness.